2004
DOI: 10.1590/s0100-67622004000600019
|View full text |Cite
|
Sign up to set email alerts
|

Momentos-L: teoria e aplicação em hidrologia

Abstract: 1RESUMO -Esta nota técnica foi redigida com o objetivo de apresentar o método momentos-L, que tem sido proposto para o cálculo dos parâmetros das principais distribuições de probabilidades utilizadas em estudos hidrológicos. Também foi seu objetivo inferir sobre o tipo de distribuição estatística mais empregada em aplicações específicas. Com base na revisão, pôde-se concluir que, ao analisar dados de eventos extremos, é recomendável testar a aderência, pelo menos, das seguintes distribuições de três parâmetros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…Valverde et al (2004) reported that the L-moments method is similar to the conventional method of moments, however, the former derives from probability weighted moments. This method applies linear combinations of the asymmetry, the kurtosis and the coefficient of variation, thus producing a more reliable statistical system.…”
Section: L-moments Techniquementioning
confidence: 99%
“…Valverde et al (2004) reported that the L-moments method is similar to the conventional method of moments, however, the former derives from probability weighted moments. This method applies linear combinations of the asymmetry, the kurtosis and the coefficient of variation, thus producing a more reliable statistical system.…”
Section: L-moments Techniquementioning
confidence: 99%
“…For instance, according to VALVERDE et al (2004), the parameters of some distributions, such as the GEV, should be estimated using the L-moments derived from the moments weighted by probability. In addition, as described by QUEIROZ & CHAUDHRY (2006) the LH can be used for evaluating the upper tail of the GEV distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Para Valverde (2004), o estudo de distribuição de frequência de vazões máximas e mínimas necessita do uso de distribuições estatísticas. Segundo Leme (2003), os processos hidrológicos, como a vazão de um riosão aleatórios, sendo assim, o tratamento dos dados e informações com base estatística devem ser realizados a partir de distribuições teóricas de probabilidade aplicadas as séries hidrológicas.…”
Section: -Introduçãounclassified